The My Diabetes Care Patient Portal Intervention: Usability and Pre-Post Assessment - Martinez, William; Hackstadt, Amber J.; Hickson, Gerald B.; Knoerl, Thomas; Rosenbloom, S. Trent; Wallston, Kenneth A.; Elasy, Tom A. (Applied Clinical Informatics, 2021)
Background My Diabetes Care (MDC) is a novel, multifaceted patient portal intervention designed to help patients better understand their diabetes health data and support self-management. MDC uses infographics to visualize and summarize patients' diabetes health data, incorporates motivational strategies, and provides literacy level–appropriate educational resources.Objectives We aimed to assess the usability, acceptability, perceptions, and potential impact of MDC.Methods We recruited 69 participants from four clinics affiliated with Vanderbilt University Medical Center. Participants were given 1 month of access to MDC and completed pre- and post-questionnaires including validated measures of usability and patient activation, and questions about user experience.Results Sixty participants completed the study. Participants' mean age was 58, 55% were females, 68% were Caucasians, and 48% had limited health literacy (HL). Most participants (80%) visited MDC three or more times and 50% spent a total of ≥15 minutes on MDC. Participants' median System Usability Scale (SUS) score was 78.8 [Q1, Q3: 72.5, 87.5] and significantly greater than the threshold value of 68 indicative of “above average” usability (p < 0.001). The median SUS score of patients with limited HL was similar to those with adequate HL (77.5 [72.5, 85.0] vs. 82.5 [72.5, 92.5]; p = 0.41). Participants most commonly reported the literacy level–appropriate educational links and health data infographics as features that helped them better understand their diabetes health data (65%). All participants (100%) intended to continue to use MDC. Median Patient Activation Measure® scores increased postintervention (64.3 [55.6, 72.5] vs. 67.8 [60.6, 75.0]; p = 0.01).Conclusion Participants, including those with limited HL, rated the usability of MDC above average, anticipated continued use, and identified key features that improved their understanding of diabetes health data. Patient activation improved over the study period. Our findings suggest MDC may be a beneficial addition to existing patient portals.
Keywords: patient portal; interfaces and usability; patient engagement; diabetes mellitus; patient self-care